Type 1 diabetes and diet-induced obesity predispose C57BL/6J mice to PM2.5-induced lung injury: a comparative study - Shen Chen; Miao Li; Rui Zhang; Lizhu Ye; Yue Jiang; Xinhang Jiang; Hui Peng; Ziwei Wang; Zhanyu Guo; Liping Chen; Rong Zhang; Yujie Niu; et al. (Particle and Fibre Toxicology, 2023)
Abstract Background Pre-existing metabolic diseases may predispose individuals to particulate matter (PM)-induced adverse health effects. However, the differences in susceptibility of various metabolic diseases to PM-induced lung injury and their underlying mechanisms have yet to be fully elucidated. Results Type 1 diabetes (T1D) murine models were constructed by streptozotocin injection, while diet-induced obesity (DIO) models were generated by feeding 45% high-fat diet 6 weeks prior to and throughout the experiment. Mice were subjected to real-ambient PM exposure in Shijiazhuang City, China for 4 weeks at a mean PM2.5 concentration of 95.77 µg/m3. Lung and systemic injury were assessed, and the underlying mechanisms were explored through transcriptomics analysis. Compared with normal diet (ND)-fed mice, T1D mice exhibited severe hyperglycemia with a blood glucose of 350 mg/dL, while DIO mice displayed moderate obesity and marked dyslipidemia with a slightly elevated blood glucose of 180 mg/dL. T1D and DIO mice were susceptible to PM-induced lung injury, manifested by inflammatory changes such as interstitial neutrophil infiltration and alveolar septal thickening. Notably, the acute lung injury scores of T1D and DIO mice were higher by 79.57% and 48.47%, respectively, than that of ND-fed mice. Lung transcriptome analysis revealed that increased susceptibility to PM exposure was associated with perturbations in multiple pathways including glucose and lipid metabolism, inflammatory responses, oxidative stress, cellular senescence, and tissue remodeling. Functional experiments confirmed that changes in biomarkers of macrophage (F4/80), lipid peroxidation (4-HNE), cellular senescence (SA-β-gal), and airway repair (CCSP) were most pronounced in the lungs of PM-exposed T1D mice. Furthermore, pathways associated with xenobiotic metabolism showed metabolic state- and tissue-specific perturbation patterns. Upon PM exposure, activation of nuclear receptor (NR) pathways and inhibition of the glutathione (GSH)-mediated detoxification pathway were evident in the lungs of T1D mice, and a significant upregulation of NR pathways was present in the livers of T1D mice. Conclusions These differences might contribute to differential susceptibility to PM exposure between T1D and DIO mice. These findings provide new insights into the health risk assessment of PM exposure in populations with metabolic diseases.